2017
DOI: 10.24820/ark.5550190.p009.965
|View full text |Cite
|
Sign up to set email alerts
|

Metal-free syntheses of oxazoles and their analogues based on λ3-iodane-mediated cycloisomerization/functionalization reactions or [2+2+1] cycloaddition type reactions

Abstract: As a metal-free construction of oxazoles and furans concomitant with the introduction of oxygen functional groups or fluorine atoms into the side chains, we have developed λ 3 -iodane-mediated cycloisomerization/functionalization reactions of propargyl compounds. In these reactions, aryl-λ 3 -iodane ArI(X)Y works not only as a donor of heteroatomic functional groups but also as an activator of carbon-carbon triple bonds. Therefore, this methodology is not required any transition metal catalysts, which are freq… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2017
2017
2021
2021

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 39 publications
0
7
0
Order By: Relevance
“…With the C−C triple bond activation [25] advantage by Aryl λ 3 ‐iodanes over metal‐catalysed reaction, Akio Saito [26] reported a novel methodology of oxazoles 17 synthesis from propargyl species 16 via [2+2+1] cycloaddition [27] type reaction with introduced an acyloxy group (Scheme 7). The substituted amides with aromatic and aliphatic groups were well‐tolerated under standardised reaction conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…With the C−C triple bond activation [25] advantage by Aryl λ 3 ‐iodanes over metal‐catalysed reaction, Akio Saito [26] reported a novel methodology of oxazoles 17 synthesis from propargyl species 16 via [2+2+1] cycloaddition [27] type reaction with introduced an acyloxy group (Scheme 7). The substituted amides with aromatic and aliphatic groups were well‐tolerated under standardised reaction conditions.…”
Section: Literature Reviewmentioning
confidence: 99%
“…The oxazoline nucleus is present in many heterocyclic compounds that have found important applications in medicinal and materials chemistry. 14,51,53,54 Numerous synthetic strategies for the construction of the oxazoline ring have been explored. Particularly important are synthetic approaches using hypervalent iodine reagents, such as (diacetoxyiodo)arenes, [55][56][57][58][59][60][61][62][63][64][65] iodosylarenes, 66 (difluoroiodo)arenes, 67 in situ generated iodine(III) species, [68][69][70][71][72][73] or iodonium ylides.…”
Section: Synthesis Of Oxazolinesmentioning
confidence: 99%
“…Oxazoles have found numerous applications in chemical and biomedical sciences, and many synthetic procedures for oxazole ring formation from various precursors have been developed. 10,16,28,30,51 Particularly important are methods based on the use of hypervalent iodine reagents such as (diacetoxyiodo)benzene, [76][77][78][79][80][81][82][83][84][85][86][87] [bis(trifluoroacetoxy)iodo]benzene, 79,[88][89][90][91] iodosylbenzene, [92][93][94][95] [hydroxy(tosyloxy)iodo]arenes, [96][97][98][99] recyclable iodine(III) compounds, 100 in situ generated iodine(III) species, 76,[101][102][103][104][105][106] and iodonium ylides. [107][108][109][110][111][112][113] The hypervalent-iodine(III)-mediated cyclization of Npropargylamides represents a useful synthetic methodology for the construction of the oxazole nucleus.…”
Section: Scheme 9 Preparation Of 4-oxazoline Compounds From Iodonium mentioning
confidence: 99%
See 1 more Smart Citation
“…As part of our research on the syntheses of heterocycles by iodine(III)-mediated/catalyzed oxidative cycloaddition reactions [ 17 19 ], we have found that iodine(III) reagents are effective in the oxidation of N–O bonds of oximes in the cycloaddition reaction of in situ formed nitrile oxides [ 20 21 ]. Although Adam and Bottke’s group have demonstrated that (diacetoxyiodo)benzene (DIB) and iodosylbenzene are applicable to the ene reactions of acylnitroso species derived from hydroxamic acids [ 22 ], the iodine(III)-mediated oxidative cycloaddition reaction of hydroxamic acids with dienes is still unknown.…”
Section: Introductionmentioning
confidence: 99%